Advances in endovascular neuro-oncology: endovascular selective intra-arterial (ESIA) infusion of targeted biologic therapy for brain tumors. (1st November 2019) - Srinivasan, Visish M; Lang, Frederick F; Chen, Stephen R; Chen, Melissa M; Gumin, Joy; Johnson, Jeremiah; Burkhardt, Jan-Karl; Kan, Peter
Abstract : Background: Malignant gliomas continue to have a poor clinical outcome with available therapies. In the past few years, new targeted biologic therapies have been studied, with promising results. However, owing to problems with ineffective IV delivery of these newer agents, an alternative, more direct delivery mechanism is needed. Simultaneously, advancements in neuroendovascular technology have allowed endovascular selective intra-arterial approaches to delivery. This method has the potential to increase drug delivery and selectively target tumor vasculature. Objective: To review the history of IA therapy for brain tumors, prior failures and successes, the emergence of new technologies and therapies, and the future direction of this young field. Methods: A comprehensive literature search of two databases (PubMed, Ovid Medline) was performed for several terms including 'brain tumor', 'glioma', and 'endovascular intra-arterial'. Forty-five relevant articles were identified via a systematic review following PRISMA guidelines. Additional relevant articles were selected for further in-depth review. Emphasis was given to articles discussing selective intra-arterial intracranial delivery using microcatheters. Results: Endovascular intra-arterial therapy with chemotherapy has had mixed results, with currently active trials using temozolomide, cetuximab, and bevacizumab. Prior attempts at IA chemotherapy with older-generation medications did not surpass the efficacy of IV administration. Advances in neuro-oncology have brought to the forefront new targeted biologic therapies. Conclusions: In this review, we discuss the emerging field of endovascular neuro-oncology, a field that applies modern neuroendovascular techniques to the delivery of new therapeutic agents to brain tumors. The development of targeted therapies for brain tumors has been concurrent with the development of microcatheter technology, which has made superselective distal intracranial arterial access feasible and safe.